2013
DOI: 10.1016/j.jobcr.2013.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar bone graft with Platelet Rich Plasma in cleft alveolus

Abstract: We conclude that on preliminary investigations, PRP seems to enhance bone formation in alveolar clefts when admixed with autologous cancellous bone harvested from the iliac crest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 14 publications
0
27
0
Order By: Relevance
“…This result agreed with Chandan et al, (2018), who reported that, pain persisted longer in patients who were treated with autgenous graft than in patients who was treated with the combined use of PRF and autogenous graft. (16) According to this study, all patients gained uneventful closure of the alveolar arch and no oronasal fistula had been detected at the end of the follow-up (i.e. after 6 months).…”
Section: Discussionmentioning
confidence: 57%
“…This result agreed with Chandan et al, (2018), who reported that, pain persisted longer in patients who were treated with autgenous graft than in patients who was treated with the combined use of PRF and autogenous graft. (16) According to this study, all patients gained uneventful closure of the alveolar arch and no oronasal fistula had been detected at the end of the follow-up (i.e. after 6 months).…”
Section: Discussionmentioning
confidence: 57%
“…Surgical correction of the defects using grafts like iliac crest with or without growth factor and placement of implants was an expensive and time taking procedure for this patient. 6 Some authors suggested alloplast graft with collagen membrane provides good result in cleft alveolus. 7 In this clinical situation, conventional removable prosthesis or fixed prosthesis was not a feasible option.…”
Section: Discussionmentioning
confidence: 99%
“…1 The bar should be at least 2 mm in height for sufficient strength to support the removable portion of restoration. 6 The removable component includes acrylic teeth on acrylic denture base. There are various treatment options to rehabilitate such kind of challenging cases like removable partial denture, cast partial denture, implant placement after bone augmentation etc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alveolar clefts are congenital bone defects in the alveolar bone that affect 75% of cleft lip or cleft lip and palate patients (114). The combination of iliac graft and PRP reduce bone resorption compared to iliac graft alone in patients requiring alveolar cleft augmentation (95, 96). On the other hand, adding PRF to iliac bone grafts, did not benefit maxillary alveolar bone thickness, height, and density or the percentage of newly formed bone (97, 98).…”
Section: Regenerative Properties Of Platelet Granulesmentioning
confidence: 99%